Unexpected voriconazole toxicity due to nirmatrelvir/ritonavir: a case report on drug-drug interaction and the role of therapeutic drug monitoring - López-Hernández, J.; Guisado-Gil, A. B.; Mejías-Trueba, M.; Herrera-Hidalgo, L.; Reina-Martínez, F. J.; Gil-Navarro, M. V. (Frontiers in Pharmacology, 2025)
Voriconazole is a triazole antifungal used for invasive fungal infections, particularly invasive aspergillosis. Its metabolism is primarily mediated by CYP2C19, with CYP3A4 and CYP2C9 also involved. Nirmatrelvir/ritonavir, an oral antiviral for COVID-19, inhibits CYP isoforms potentially altering the metabolism of co-administered drugs. We report a case of an immunosuppressed patient with SARS-CoV-2 pneumonia and invasive aspergillosis treated with voriconazole and nirmatrelvir/ritonavir. Unexpectedly, voriconazole plasma concentrations increased significantly (7.78 mg/L) instead of the anticipated decrease, leading to temporary discontinuation. Therapeutic drug monitoring (TDM) guided dose adjustments until optimal levels (2 mg/L) were achieved. After 13 days, the patient recovered from COVID-19, with clinical improvement of aspergillosis. This case highlights the importance of pharmacokinetic monitoring and drug-drug interaction assessment in critically ill patients.